Dekalog - Kieślowski, Krzysztof; Zdort, Wieslaw; Klosinski, Edward; Sobocinski, Piotr; Baranowski, Henryk; Klata, Wojciech; Janda, Krystyna (Arrow Films, 2016)
Krzysztof Kieslowski's "Dekalog" is one of the greatest achievements of the late twentieth century as much an intricate work of moral philosophy as it is a collection of psychologically riveting narratives. Each standalone story revolves around the consequences arising from a breach of one of the Ten Commandments, but this is no finger-wagging religious tract: Kieslowski was one of film history's keenest observers of human nature, and his troubled, vainglorious, self-deceiving, deeply flawed characters (many played by some of Poland's finest character actors) are all too universally recognisable. "Dekalog" is merely the highlight of a box set that compiles virtually all of Kieslowski's television work, starting with his first professional short fiction film and continuing with four feature-length pieces that are in every way as probing and incisive as his better-known cinema films. [Cover]